A arborização viária no município de Pato Branco – PR e suas relações com solos urbanos e percepção dos moradores - Cadorin, Danielle Acco (2013)
The street forestation is an important environmental element that mitigates the effects which the process of urbanization on the environment causes. There are various factors that relate to the good development of trees in cities; among them are the management by the government, the residents’ perception and the environmental conditions in which the species are evolving, especially soil conditions. Thus, the present study aimed to evaluate relationships between soil, residents and the arboreal species regarding the urban forestry in Pato Branco. Therefore, it was delimited as study area five neighborhoods with different characteristics of location and income in the county: Centro, La Salle, Pinheiros, Aeroporto e Veneza. Lagerstroemia indica L. (crape myrtle), Schinus molle L. (california pepper tree), and Bauhinia variegata L. (orchid tree) were the species studied, chosen by their representation in the forestation of the city. It was evaluated the soil used by 114 tree individuals in the five neighborhoods and 123 semi-structured questionnaires were administered in order to understand how the residents of these neighborhoods perceive the urban forestation. The survey results indicate that there is a great variability concerning the characteristics of the soils studied which present incorporation of anthropogenic materials, inversion of horizons and absence of decaying organic layer. The results of sieve analysis showed that despite the variability of textures in evaluated points, most soils analyzed fit in the texture class of very clayey or loamy. The urbanization process in the city of Pato Branco has fundamentally altered the chemical properties of soils of the studied species, since most of them showed relative enrichment in exchangeable bases, which antagonizes with the low natural fertility of soils in Pato Branco. There were also chemical differences regarding the impermeable soils by pavement and the ones not impermeable, the impermeable soils presented lower levels of organic matter and higher values of Ca and pH. The soils in the center area seem to be the most affected by the urbanization process, where there is a higher percentage of sand added to the soil, and greater amount of waterproofing materials coming from civil construction. Regarding the perception of residents, in general the interviewees seem to recognize the importance and function of urban forestation. Among the problems perceived by the research subjects, many are technical in nature and could be avoided through an efficient planning. Other observed problems are cultural, more complex and difficult to solve. Residents prefer mainly the species that have attractive such as exuberant blooms and they seem to appreciate trees that they chose by themselves to have in front of their homes. Therefore, it is important to adjust the strategies adopted by the government to the local needs, preserve the cultural aspects, and contemplate besides the technical aspects related to forestation, other aspects in a ludic way, to attract and encourage people to commit themselves with forestation.